The effects of different spices on chemical, biochemical, textural and sensory properties of White cheeses during ripening - Tarakci, Zekai (Array, 2019)
The aim of this study was to test the effects of various spices on the physicochemical and sensory properties of white cheese. Six different white cheeses were produced by incorporating the spices of black cumin, mint, thyme, red pepper and isot pepper at a ratio of 3 % (w/v) of the cheese milk. All cheeses were vacuum-packed and ripened at 4±1°C. On the 2nd, 15th, 30th, 60th and 90th days of ripening, dry matter, fat, pH, titratable acidity, salt, total proteins, ripening index, non-protein nitrogen rate, amino nitrogen rate, electrophoretic casein fractions, textural and sensory properties were determined. Isot pepper and black cumin increased the proteolysis rates of white cheeses with higher degradation rates on β-casein fraction, indicating that these cheese samples had more pronounced ripening. On the other hand, thyme and isot pepper were more effective on αs1-casein fraction. All tested spices, except isot pepper, contributed to the sensory properties of white cheeses, by increasing the consumer acceptance. This study reveals spice addition had positive effects on chemical, biochemical and sensory characteristics of white cheese, and thus, white cheese with spice addition is an alternative novel product with a good potential.